The Influence of Self-Esteem and Brand Trust to Optimize Brand Loyalty Based on Social Identity Theory in Generation Y & Z - Anggraini, Melfi Cahya; Marsasi, Endy Gunanto (Jurnal Ecogen, 2024)
The fashion industry is experiencing rapid development and innovation. This thrives thanks to the creative contributions of Indonesia's diverse young generation, shaping the country's fashion landscape trends in 2023.  The purpose of this study is to investigate the influence of brand trust, brand love, self-esteem, and susceptibility to normative influences on brand loyalty in the fashion industry among Generation Y & Z.  Purposive sampling was the method used for sampling in this study by distributing questionnaires electronically and obtaining 150 respondents for the main research. Researchers added the Brand Trust variable as a novelty. Social Identity Theory is used in this research as a grand theory. This research was analyzed with IBM SPSS 29 and using Structural Equating Modeling (SEM) on AMOS 24 software.  The study's findings indicate that brand trust significantly influences brand loyalty which is mediated by brand love. Brand love positive and significantly influences self-esteem. Meanwhile, self-esteem has insignificant effect on brand loyalty. The implication of this research is a contribution to fashion industry decision-makers regarding consumer behavior in Generation Y & Z.